Effect of different roller end-flange constructions on the fatigue life of the cylindrical roller bearings: A novel flange deformation formula - Bayrak, Ramazan; Sagirli, Ahmet (POLISH MAINTENANCE SOC, 2023)
This paper performs the fatigue life analysis of the radial Cylindrical Roller Bearings (CRBs) with consideration of various roller end-flange shapes such as toroidal-toroidal, spherical-toroidal, and spherical conical. A novel formula for each flange contact deformation in cylindrical roller bearing with different roller end-flange geometry including toroidal geometry is developed. Inner ring misalignment angle and radial deflection results obtained from the present study are verified with numerical and experimental results from the literature. The results approach to that of literature when the flange is changed from toroidal geometry to conical geometry. Using formulas developed in the present study, the effect of various roller end-flange geometries on the bearing life is investigated for different external loadings. It is observed that the bearing life increases when the roller end and flange are changed to toroidal geometry.
Keywords: cylindrical roller bearing; roller end-flange design; fatigue life; misalignment; INTERNAL CLEARANCE; LOAD DISTRIBUTION; EHL ANALYSIS; HIGH-SPEED; CONTACT; PREDICTION; STRESSES; FRICTION; BALL; Engineering